2015
DOI: 10.1109/tpel.2014.2376778
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of the Forward Operation of 4H-SiC Vertical DMOSFET in the Safe Operating Temperature Range

Abstract: A new analytical model of 4H-SiC DMOSFETs that is useful to explore their thermal stability is presented. The model is capable to describe, with closed form equations, the DC forward behavior of devices in a wide temperature range, including the effects of parasitic resistances and oxide interface traps. The model allows to analyze the on-set of electro-thermal stability of 4H-SiC DMOSFETs both in triode and in saturation region, and to monitor the impact of the series resistance and traps on reliable operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…On the other hand, when the temperature increases, the probability of re-emission will be higher, and the trapping will not occur [18]. The measurements of Licciardo et al [5] have shown a shift in the threshold voltage to the left when the operating temperature is increased. We have modelled the interface traps/defects as consisting of both donor and acceptor interface traps distributed in the energy.…”
Section: Interface Traps/defects Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, when the temperature increases, the probability of re-emission will be higher, and the trapping will not occur [18]. The measurements of Licciardo et al [5] have shown a shift in the threshold voltage to the left when the operating temperature is increased. We have modelled the interface traps/defects as consisting of both donor and acceptor interface traps distributed in the energy.…”
Section: Interface Traps/defects Modelsmentioning
confidence: 98%
“…In our device model, the deep level density of states distribution has been assumed to be Gaussian distributed. Accordingly, the total density of states is given by [5,14,19]…”
Section: Interface Traps/defects Modelsmentioning
confidence: 99%
“…The model in [12] uses an empirical function to describe the variation of the drain resistance with drain and gate voltage and with temperature. The model presented in [13] depends on parameters which are related to the manufacturing process. In [14] a resistance model is developed which is based on the modeling approaches for silicon DMOS transistors.…”
Section: B Drain Resistancementioning
confidence: 99%
“…Recently some models have been published which try to consider the special effects occurring in SiC MOSFETs. Effects caused by interface traps are taken into account in [12] and [13]; [13] describes the influence of traps on the threshold voltage whereas [12] considers the variation of the electron mobility due to the traps. The variable drain resistance is modelled in [12]- [15]; a short discussion of these models is given in section II.B.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these improvements, overall system size is decreased yielding increased power densities with SiC MOSFETs compared to existing commercial systems utilizing Si IGBTs [9]. However, for SiC technology to displace the well-known and accepted Si devices, its performance and failure modes must be understood across all conditions expected in commercial applications [21]- [27]. Work has previously been performed to understand the effect of pulsed overcurrents on the long-term reliability of SiC MOSFETs [1], [24]; however, these results did not examine the failure mode, which must be analyzed through further testing and modeling.…”
Section: Introductionmentioning
confidence: 99%